2024
DOI: 10.19088/ids.2024.006
|View full text |Cite
|
Sign up to set email alerts
|

Social Protection Experiences of and Attitudes Towards New Urban Poor After Covid-19 in Bangladesh

Keetie Roelen,
Md. Shakil Ahmed,
Kabita Chowdhury
et al.

Abstract: The Covid-19 pandemic led to a large increase in poverty in Bangladesh, especially in urban areas. Rising food prices and high inflation rates further compounded already high levels of socioeconomic uncertainty. Social protection is vital to help mitigate the effects of crisis and make households more resilient to uncertainty. This paper provides insights into urban residents’ experiences of poverty and the support they received since the Covid-19 pandemic, and derives implications for social protection progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…One of the new programmes was the prime minister's cash support scheme which provided one-off assistance of BDT 2,500 (£22) to five million informal workers who lost their jobs on account of the crisis and were not receiving any other form of social protection. While this scheme undoubtedly helped to relieve some of the pressure, its limited nature -including the relatively low transfer level -meant that it provided only 5 per cent of the amount needed to restore pre-shock consumption level (Hebbar, Muhit and Marzi 2021;Roelen et al 2024).…”
Section: Social Protection Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the new programmes was the prime minister's cash support scheme which provided one-off assistance of BDT 2,500 (£22) to five million informal workers who lost their jobs on account of the crisis and were not receiving any other form of social protection. While this scheme undoubtedly helped to relieve some of the pressure, its limited nature -including the relatively low transfer level -meant that it provided only 5 per cent of the amount needed to restore pre-shock consumption level (Hebbar, Muhit and Marzi 2021;Roelen et al 2024).…”
Section: Social Protection Contextmentioning
confidence: 99%
“…Thirteen per cent of urban households reported help from the government, while this figure was only 3 per cent for rural households (PPRC and BIGD 2020b). Although the preexisting social protection schemes were largely rural focused, several of the studies found that government support was reported at higher levels in urban low-income areas compared to rural areas (Roelen et al 2024).…”
Section: Key Findings On Innovations For Managing Crisis Response Thr...mentioning
confidence: 99%
See 3 more Smart Citations